ANALISIS PERSEPSI MAHASISWA FAKULTAS ILMU KEBUDAYAAN UNIVERSITAS DIPONEGORO TERHADAP PENGARUH PENGGUNAAN CHAT GPT - Sari, Lutfiana Mutia; Deniswara, Falihah Serend; Panggabean, Muhammad Zidan; Hakim, Riswan Nabil; Najwa, Ayesha; Amalia, Nazhira; Wahyudi, Rizky Rahmat; Dhofier, Raden Muhamad (Yayasan Amanah Nur Aman, 2025)
This study analyzes determinants of Behavioral Intention to Use ChatGPT among undergraduate students at the Faculty of Cultural Sciences, Diponegoro University using an extended Technology Acceptance Model (TAM) framework. Through quantitative approach, data were collected from 109 respondents via Google Form questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Results revealed statistically significant positive relationships between Perceived Usefulness (β=0.32, p=0.012) and Perceived Value (β=0.28, p=0.036) with Usage Intention. Interestingly, conventional TAM variables including Perceived Ease of Use (β=0.15, p=0.073), Trust (β=0.08, p=0.664), and Attitude Toward Use (β=0.07, p=0.561) showed no significant effects in this cultural studies context. The study reveals unique adoption patterns where cultural sciences students prioritize functional utility and academic value over technical simplicity or emotional factors in AI tool usage. This research provides theoretical contributions by challenging conventional TAM assumptions in cultural studies settings, while offering practical implications for AI developers and educational technologists to enhance academic content usability and optimize interaction efficiency specific to cultural studies disciplines.